Dynamics of the last glacial maximum Antarctic ice-sheet and its response to ocean forcing - Golledge, Nicholas R; Fogwill, Christopher J; Mackintosh, Andrew N; Buckley, Kevin M (Proceedings of the National Academy of Sciences - PNAS, 2012)
Retreat of the Last Glacial Maximum (LGM) Antarctic ice sheet is thought to have been initiated by changes in ocean heat and eustatic sea level propagated from the Northern Hemisphere (NH) as northern ice sheets melted under rising atmospheric temperatures. The extent to which spatial variability in ice dynamics may have modulated the resultant pattern and timing of decay of the Antarctic ice sheet has so far received little attention, however, despite the growing recognition that dynamic effects account for a sizeable proportion of mass-balance changes observed in modern ice sheets. Here we use a 5-km resolution whole-continent numerical ice-sheet model to assess whether differences in the mechanisms governing ice sheet flow could account for discrepancies between geochronological studies in different parts of the continent. We first simulate the geometry and flow characteristics of an equilibrium LGM ice sheet, using pan-Antarctic terrestrial and marine geological data for constraint, then perturb the system with sea level and ocean heat flux increases to investigate ice-sheet vulnerability. Our results identify that fast-flowing glaciers in the eastern Weddell Sea, the Amundsen Sea, central Ross Sea, and in the Amery Trough respond most rapidly to ocean forcings, in agreement with empirical data. Most significantly, we find that although ocean warming and sea-level rise bring about mainly localized glacier acceleration, concomitant drawdown of ice from neighboring areas leads to widespread thinning of entire glacier catchments-a discovery that has important ramifications for the dynamic changes presently being observed in modern ice sheets.